The effect of social media and infodemic on mental health during the COVID-19 pandemic: results from the COMET multicentric trial - Sampogna, Gaia; Di Vincenzo, Matteo; Luciano, Mario; Della Rocca, Bianca; Albert, Umberto; Carmassi, Claudia; Carrà, Giuseppe; Cirulli, Francesca; Dell’Osso, Bernardo; Nanni, Maria Giulia; Pompili, Maurizio; Sani, Gabriele; et al. (Frontiers in Psychiatry, 2023)
On January 30, 2020, the World Health Organization (WHO) declared the status of pandemic due to the COVID-19 infection. The initial phases of the pandemic were characterized by uncertainty and public fears. In order to cope with such unexpected conditions, people adopted different coping strategies, including search for information, accessing Internet, and using social media.The present study based on the COMET collaborative research network aims to: 1) assess use of Internet and of social media among the Italian general population; 2) explore differences in web usage between people with pre-existing mental disorders and the general population; 3) identify changes over time in social media usage along the phase 1 of the pandemic; 4) identify the clinical, socio-demographic and contextual predictors of excessive use of social media.A significant increase in time spent on Internet, with an average time of 4.8±0.02 hours per day, was found in the global sample of 20,720 participants. Compared with the general population, Internet use was significantly higher in people with pre-existing mental disorders (5.2±0.1 hours vs. 4.9±0.02; p<.005). According to the multivariate logistic regression model, the risk of excessive use of social media and Internet was significantly higher in people with moderate levels of depressive symptoms (OR: 1.26, CI 95%: 0.99 to 1.59, p<.0.005); protective factors were being students (OR: 0.72, CI 95%: 0.53 to 0.96, p<.0.0029) and living in central Italy (OR: 0.46, CI 95%: 0.23 to 0.90, p<.002).The evaluation of social media and Internet use by the general population represents a first step for developing specific protective and supportive interventions for the general population, including practical suggestions on how to safely use Internet and social media.